2006
DOI: 10.1097/01.hjh.0000194117.96979.13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the white-coat effect

Abstract: The WCE may not just be limited to that narrow interval in which the patient actually sees the physician, but may generalize to the clinic setting, rendering a clinic 'resting' level invalid. While it is strongly positive in most hypertensive patients, it is frequently negative in normotensive patients. Our results suggest that improved methods of measuring blood pressure in the clinic setting are unlikely to resolve the confounding influence of the WCE, and that greater reliance will need to be placed on out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 16 publications
4
29
1
1
Order By: Relevance
“…To measure the ''real WCE'', some authors propose using methods that can record the beat-to-beat BP before, during, and after a physician visit [29,30] so that the ''confusing effect'' introduced by the patient's activity can be avoided. However, this also presents its limitations, as the BP before the physician visit may be high (as a result of the clinical environment), and therefore, the WCE may be underestimated [31]. For these reasons, the difference between CPBP (or clinic BP) and ABPM is commonly accepted to assess the severity, frequency, clinical relevance, predicting factors and other topics related to the WCE [1].…”
Section: Discussionmentioning
confidence: 99%
“…To measure the ''real WCE'', some authors propose using methods that can record the beat-to-beat BP before, during, and after a physician visit [29,30] so that the ''confusing effect'' introduced by the patient's activity can be avoided. However, this also presents its limitations, as the BP before the physician visit may be high (as a result of the clinical environment), and therefore, the WCE may be underestimated [31]. For these reasons, the difference between CPBP (or clinic BP) and ABPM is commonly accepted to assess the severity, frequency, clinical relevance, predicting factors and other topics related to the WCE [1].…”
Section: Discussionmentioning
confidence: 99%
“…Yeragani et al, 1990aYeragani et al, , 1990b and in the different contexts (Gerin et al, 2006). Findings of a few recent studies (Bo et al, 2009;Yavuz et al, 2009;Richardson et al, 2009;Vasudev et al, 2011), investigating the relationship between mood and the 'white coat effect' (normally defined by the blood pressure rise from before to during the visit, Verdecchia et al, 2002;Gerin et al, 2006), or between mood and the 'orthostatic hypotension' (generally defined by sustained drop in SBP and DBP within several minutes of active standing after supine rest, Freeman et al, 2011), also supported the hypothesis that the proposed habituation/sensitization and adaptation/maladaptation mechanisms should both be related to the moderation effect of situation-or context-specific arousal on relationships between blood pressure and mood.…”
Section: Introductionmentioning
confidence: 99%
“…For almost all subjects with hypertension, blood pressures during this window are lower than conventionally recorded pressures in the office, clinic or surgery setting [12,13]. However, blood pressures during this period are subject to stress, activity, arm movement, the effect of exercise and other activities, such as driving, all of which may have an influence on the mean level of blood pressure recorded [14].…”
Section: Daytime Windowmentioning
confidence: 92%
“…However, it has been shown that the white coat window on ABPM recordings cannot only diagnose the white coat phenomenon but also allows identification of a white coat hypertensive sub-group with significantly higher pressures, who may be at greater risk and in need of antihypertensive medication [11]. ABPM remains the method of choice for diagnosing white coat hypertension [2,11,12].…”
Section: White Coat Windowmentioning
confidence: 99%